'Existential' in Scandinavian Healthcare Journals: An Analysis of the Concept and Implications for Future Research - Nygaard, Marianne Rodriguez (Religions, 2022)
The concept of ‘existential’, used frequently in Scandinavian healthcare journals, is associated with various, often unclear, meanings, highlighting the need for a more accurate understanding of the concept. In this integrative review we analyse how the concept has been used in Scandinavian healthcare journals from 1984 to 2020, exploring the trajectory of the concept, its definitions and its applications. A secondary aim is to offer some clarity regarding how the concept may be used in future healthcare research and provide a definition of ‘existential’ based on our findings. Our findings show that while the concept is increasingly used, it is rarely defined, and there appears to be no consensus on the concept’s meaning. We categorise applications of the concept into five overarching themes: (1) Suffering and re-orientation, (2) Meaning and meaninglessness, (3) Existential philosophy in relation to health (4) Existential questions as approaches to care and (5) Usage and demarcation of existential, spiritual and religious concepts. Based on the findings, we propose a definition of the concept of ‘existential’ in the healthcare context. The study contributes to, and underscores advantages and limitations of, the use of the concept in healthcare research.